Single Euro Payments Area and its Implications on the European Small and Medium-Sized Enterprises - Andreea Avadanei (CES Working Papers, 2010)
The scope of this article is to discuss the implications of the Single Euro Payments Area from the perspective of the European SMEs. The current unpredictable and very challenging market situation has not fundamentally changed the fact that payment services need to continue modernization in order to become more flexible, agile and adapt in order to comply with its important purpose in society.SEPA is needed to ensure the new modern payment platform that can enable Europe to move beyond basic services, increase payments efficiency, embrace innovation and integrate further services in the trade process. European Small and Medium-sized Enterprises see SEPA see SEPA as an important step towards the completion of the internal market, but such a major initiative has to be well planed, must meet the practical needs of enterprises and provide, at least in the long run, positive incentives for all market participants.
Keywords: 330; Single Euro Payments Area; payments landscape; small users; Payment Services